2015
DOI: 10.1186/s12879-016-1401-x
|View full text |Cite
|
Sign up to set email alerts
|

A case report of Anisakis pegreffii (Nematoda, Anisakidae) identified from archival paraffin sections of a Croatian patient

Abstract: BackgroundThis is the first report of anisakiasis in a Croatian patient, evidenced from an archival paraffin-embedded and hematoxylin-eosin stained tissue section. Anisakiasis has been only suspected in the country based on previously detected anti-Anisakis IgE seroprevalence in the healthy coastal population, as well as an acute case where pathohistological and serological findings suggested the diseases, but the migrating larva has not been retrieved.Case presentationSeventy years-old female, operated in 199… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 60 publications
(57 reference statements)
2
40
0
1
Order By: Relevance
“…A. simplex was found in the body cavity [15]. However, A. simplex was reported in horse mackerel muscle (it has been reported that post-mortem migration of A. simplex into the flesh of some host species [23,24]), but the percentage of larvae found in this tissue varied from very low 1.8% to high 41.8% values [22,25]. It is should be emphasized that very amount of larvae in muscle may depend on the amounts of lipids in this tissue since migration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A. simplex was found in the body cavity [15]. However, A. simplex was reported in horse mackerel muscle (it has been reported that post-mortem migration of A. simplex into the flesh of some host species [23,24]), but the percentage of larvae found in this tissue varied from very low 1.8% to high 41.8% values [22,25]. It is should be emphasized that very amount of larvae in muscle may depend on the amounts of lipids in this tissue since migration.…”
Section: Discussionmentioning
confidence: 99%
“…Mladineo et al [24] suggested that the hosts have a diet which may affect the selection of the larvae for a microhabitat (visceral organs and body cavity or muscle). The species which feed on euphausiids presented consistently low proportions of larvae in muscle and piscivorous fishes had larvae more widely distributed [6,27].…”
Section: Discussionmentioning
confidence: 99%
“…Anisakis simplex and Anisakis pegreffii) by humans can cause anisakiasis and more than 20,000 cases have been reported worldwide, over 90% from Japan, and the rest from Asia, Europe, America and New Zealand. Anisakid larvae burrow into the stomach wall and elicit an inflammatory response which causes acute ulceration, nausea, vomiting and epigastric pain [2][3][4][5]. The histological studies of rat stomach tissue infected by Anisakis typica found epithelial damage, bleeding within the submucosal layer, inflammation of the stomach and decreased numbers of mucous cap cells, which comprise the gland-containing, mucus-membrane layer covering the surface of the stomach [6].…”
Section: Introductionmentioning
confidence: 99%
“…Nine species have so far been detected genetically as belonging to the genus Anisakis . Among these, Anisakis simplex (sensu stricto ) and Anisakis pegreffii are shown to play a zoonotic role in humans . Anisakis pegreffii infection can provoke gastric (GA), intestinal (IA) and gastroallergic anisakiasis (GAA) …”
Section: Introductionmentioning
confidence: 99%